2003
DOI: 10.1901/jaba.2003.36-105
|View full text |Cite
|
Sign up to set email alerts
|

Use of the High‐probability Instructional Sequence and Escape Extinction in a Child With Food Refusal

Abstract: We used the high‐probability (high‐p) instructional sequence with and without escape extinction in the treatment of food refusal. Acceptance increased and refusal decreased only with the introduction of escape extinction. These results raise important questions about the high‐p sequence in the treatment of food refusal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
69
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 4 publications
3
69
0
2
Order By: Relevance
“…While positive reinforcement contingencies have been demonstrated to be effective for the treatment of individuals with food selectivity (Riordan, Iwata, Wohl, & Finney, 1980;Levin & Carr, 2001), several studies have also shown that positive reinforcement, when implemented alone, is ineffective in treating food refusal (Patel, Piazza, Martinez, Volkert, & Sanatana, 2002;Dawson, Piazza, Sevin, Gulotta, Lerman, & Kelly, 2003;Piazza, Patel, Gulotta, Sevin, & Layer, 2003). While the latter studies concluded positive reinforcement as being ineffective for the treatment of feeding problems, it is possible the stimuli used in these studies may not have functioned as potent reinforcers to effectively compete with the reinforcer produced by escaping the demand to eat non-preferred foods.…”
Section: Empirically Validated Treatments: Escape Extinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…While positive reinforcement contingencies have been demonstrated to be effective for the treatment of individuals with food selectivity (Riordan, Iwata, Wohl, & Finney, 1980;Levin & Carr, 2001), several studies have also shown that positive reinforcement, when implemented alone, is ineffective in treating food refusal (Patel, Piazza, Martinez, Volkert, & Sanatana, 2002;Dawson, Piazza, Sevin, Gulotta, Lerman, & Kelly, 2003;Piazza, Patel, Gulotta, Sevin, & Layer, 2003). While the latter studies concluded positive reinforcement as being ineffective for the treatment of feeding problems, it is possible the stimuli used in these studies may not have functioned as potent reinforcers to effectively compete with the reinforcer produced by escaping the demand to eat non-preferred foods.…”
Section: Empirically Validated Treatments: Escape Extinctionmentioning
confidence: 99%
“…Seeing as food selectivity has been previously conceptualized as a form of noncompliance in which the child refuses and escapes eating a sufficient variety of foods (Dawson et al, 2003), interventions utilizing escape extinction (i.e., non-removal of the spoon; NRS) have been widely researched and empirically validated as being effective in increasing the food consumption of individuals with food selectivity and related food refusal.…”
Section: Empirically Validated Treatments: Escape Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-p sequence is used in various ways and has produced inconsistent outcomes in the feeding disorders literature, however. Dawson et al (2003) evaluated the high-p sequence with a 3-year-old girl who engaged in total food refusal and found that the high-p sequence had no impact when used in isolation and, moreover, that the high-p sequence did not add to the effectiveness of escape extinction (EE). Patel et al (2006) evaluated the effects of the high-p sequence on the acceptance of foods and inappropriate behavior with three young children with feeding difficulties.…”
mentioning
confidence: 99%
“…Vaz et al (2011) increased self-feeding by the removal of non-preferred food after one self-fed bite. The literature includes research that evaluates a variety of reinforcement procedures that have shown to be effective when treating feeding problems (Dawson et al 2003;Piazza et al 2004).…”
mentioning
confidence: 99%